(untitled) (European Journal of Economics, Finance and Business Development, 2023)
An artistic image arises not only as a form of visual representation of reality, but also as a way of reproducing it in a bright, concretely emotional form through a certain aesthetic ideal position. When creating an artistic image, the author relies on the figurative capabilities of words, their ability to express visual, tactile, auditory, motor and other content. The article talks about the means of creating an artistic and psychological image. The significance of such elements of a work of art as the portrait of the hero, his actions, speech, biography, etc. is assessed.